Analisis Kemampuan Berpikir Kritis Siswa Kelas X IPA Di SMA Harapan Bangsa Tanjung Morawa Pada Mata Pelajaran Biologi - Maulidya Nurliana; Khairuna Khairuna; Miza Nina Adlini (LPPM Politeknik Pratama, 2023)
This study aims to find out the critical thinking skills of class X IPA students at Harapan Bangsa Tanjung Morawa High School in the matter of ecosystems. This research is a qualitative descriptive study. The instruments used are critical thinking test questions, observation sheets, interviews and documentation. Data collection was carried out in April 2023. The sample used in this research was class X Science students, totaling 28 students. The research results show that students' critical thinking abilities in class X Science are relatively low with a percentage of 72.6⁒. The critical thinking indicator that has the highest percentage is the strategy and tactics indicator with a percentage of 83⁒ and the lowest indicator is the conclusion indicator with a percentage of 62⁒. Other indicators are providing simple explanations with a percentage of 78⁒, indicators providing further explanations 64⁒, and indicators of building basic skills 76⁒.